The state and development trends of the informal services market in the Russia in the era of the COVID-19 pandemic - I. A. Yurasov; M. A. Tanina; V. A. Yudina; E. V. Kuznetsova (Вестник университета)
Many experts expressed their point of view about the harmful impact of the global COVID-19 pandemic on the economy. Without disputing this position, which is popular in Russian and foreign media, the authors have been conducted research on the shadow market of services in 19 regions of Russia in 2020 and 2021, and have been concluded that the global pandemic has an extremely insignificant negative impact on the shadow market of services in Russia. The majority of shadow respondents did not note a significant decrease in the level of income due to the pandemic, nor a change in professional employment, nor a significant change in the level of competition. The reasons for this state of affairs became: high social mobility, social activity, high adaptability of the shadow market to any crises and changes than in the official sectors of the economy, a high level of trust between subjects and consumers of services in this sector of the economy, a high speed of reaction of this market to the needs of customers.